PERANCANGAN APLIKASI PROGRAM LOYALITAS PELANGGAN BERBASIS WEB PADA BI COFFEE - Keneth Langit Baranduda; Rayhan Arjuno Wibowo; Iktiar Jerryansyah Putra; Wasis Haryono (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research develops a web-based application for a customer loyalty program at Bi Coffee, a growing food and beverage business in the South Tangerang area. The approach used includes direct observation, in-depth interviews, and a review of relevant literature. The designed system can digitally record customer points, provide a reward exchange feature, and display the latest promotional information. The application was built using React, Node.js, Express, and PostgreSQL technologies, supported by UML diagrams such as use case, activity, and ERD. In conclusion, this application effectively replaces the manual recording previously used while significantly improving operational efficiency and customer experience.